Fabrication of Highly Sensitive Porous PDMS Pressure Sensor through Control of Rheological Properties - Jang, Yunseok; Lee, Seoung-Hyun; Lee, Youn-Ki (Meeting abstracts (Electrochemical Society), 2025)
Population aging is a notable global social phenomenon that is progressing rapidly. Currently, Japan, Finland and Italy have the highest percentages of elderly people. Within the Organization for Economic Co-operation and Development (OECD), Greece, Korea, Poland, Portugal, Slovenia, and Spain are noted for their accelerated aging rates. Outside the OECD, Brazil, China, and Saudi Arabia are among the countries experiencing the fastest aging rates. [1,2] Caring for this aging population has become a global priority, with a strong emphasis on cost-effectiveness. Pressure sensors are particularly significant as they offer crucial, indirect information about major health conditions at minimal expense, monitoring pressures within the brain, blood, vessels, and organs. [3] Consequently, pressure sensors are anticipated to play a pivotal role in the care and management of the elderly population. A pressure sensor is electronic devices that converts pressure signals into corresponding electrical signals, such as resistive, piezoelectric, triboelectric, or capacitive electrical signals. [4] Capacitive pressure sensors are particularly noted for their linear response, distinguishing then from resistive, piezoelectric, and triboelectric sensors, which often exhibit nonlinearity. [5] This distinction can be attributed to the relationship between capacitance per unit area and thickness, expressed by the following equation; C=e r e o /d where e r is the relative dielectric constant of the dielectric layer, e o is the permittivity of free space, and d is the thickness of the dielectric layer. [6] Capacitance per unit area is varies inversely with thickness, and capacitive pressure sensors demonstrate excellent linear response to external stimuli. Due to its significant thickness variation in response to external stimuli, elastomers such as polydimethylsiloxane (PDMS), the most commonly used types, were selected as the sensing material in this study. Achieving a sensitive sensor with a high signal-to-noise ratio requires the elastomer to change thickness readily even under weak forces. Previous research has explored enhancing sensitivity to external stimuli by introducing pores on the surface and within the structure of the elastomer.[7-8] Surface pores enhance the sensitivity of pressure sensors by creating microscopic voids where the elastomer can deform under external pressure. This effect has been demonstrated using pyramidal and wrinkled microstructures by Z. Bao et al.[7], and H. S. Lee et al.[8], respectively. Additionally, research has shown that internal pores within the elastomer also facilitate deformation in response to external forces. These studies collectively indicate that introducing pores either within or on the surface of an elastomer enhance its responsiveness to external stimuli. As external force increases, surface pores on the elastomer deform, enlarging the contact area between the electrode and the elastomer. In contrast, when pores are situated inside the elastomer, the change in contact area between the electrode and the elastomer diminishes with increasing external force compared to surface pores. Consequently, when pores are internal to the elastomer, a more linear response is observed upon application of external force compared to when pores are located on the elastomer surface. In this study, we propose a method to enhance sensitivity to applied force by creating pores within the elastomer. By carefully controlling the rheological properties of the elastomer, we successfully fabricated elastomers with two- or three-dimensional internal pores. We found pore formation transitions from two-dimensional (2D) to three-dimensional (3D) under specific conditions. To evaluate the impact of internal pores on the pressure sensitivity of the elastomer, a comparative analysis was performed using an elastomer without internal pores. References Rudnickaa, E.; Napierałab, P.; Podfigurnab, A.; Męczekalskib, B.; Smolarczyka, R.; Grymowicz, M. Maturitas , 2020 , 139, 6-11. OECD, Elderly Population (Demography), (2020), https://doi.org/10.1787/8d805ea1-en (Accessed on 19 January 2020). Li, R.; Zhou, Q.; Bi, Y.; Cao, S.; Xia, X.; Yang, A.; Li, S.; Xia, X. Sensors and Actuators A : Physical , 2021 , 321, 112425. Gong, S.; Yap, L. W.; Zhu, Y.; Zhu, B.; Wang, Y.; Ling, Y.; Zhao, Y.; An, T.; Lu, Y.; Cheng, W. A. Adv. Funct. Mater . 2020 , 30, 1910717. Claver, U. P.; Zhao, G. Adv. Eng. Mater. 2021 , 23, 2001187. Sze, S. M. “Semiconductor Device Physics and Technology (2nd. Ed),” Wiley and Sons, Chap. 6, 2001. Ruth, S. R. A.; Beker, L.; Tran, H.; Feig, V. R.; Matsuhisa, N.; Bao, Z. Adv. Funct. Mater. 2020 , 30, 1903100. Baek, S.; Jang, H.; Kim, S. Y.; Jeong, H.; Han, S.; Jang, Y.; Kim, D. H.; Lee, H. S. RCS Adv. , 2017 , 7, 39420. Acknowledgments： This study was supported by the R&D program of the Korea Research Council for Industrial Science and Technology of Republic of Korea (Grant 2020M3H4A310631922/ K_G012002245203/ G02P23630000812/ K_G012000702706/ GTL24011-710/ NK249G/ KN029E).